Dialektyka My/Oni w kontekście polskim, czyli rzecz o tym, dlaczego potrzebny nam agonizm - Jastrząb, Patryk (Kultura-Społeczeństwo-Edukacja, 2020)
Jastrząb Patryk, The relationship between We/They dialectics and agonism in Polish context. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 245–263, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.16. I focused on the unconstrained but established in the theory reflection on We/They dialectics, which was analysed for its antagonistic foundation as being understood in the Polish context. However, I did not only concentrate on presenting the socio-political perspective of this subject as I have adopted a more contemplative, philosophical approach. Therefore political reality was only a pretext for me to tell a reader about a much more fundamental conflict concerning our values and freedom. I concluded the consideration with stating the fact of the possibility of existence of agonistic diversity among democratic variety.